Definitive radiotherapy alone over 60 Gy for patients unfit for combined treatment to stage II-III non-small cell lung cancer: retrospective analysis. Issue 1 (December 2015) - Joo, Ji; Song, Si; Kim, Su; Jeong, Yuri; Jeong, Seong-Yun; Choi, Wonsik; Choi, Eun
Abstract Background Elderly patients with non-small cell lung cancer (NSCLC) are frequently treated with radiation therapy (RT) alone, due to poor performance status or underlying disease. We investigated the effectiveness of RT over 60 Gy administered alone to NSCLC patients who were unfit or rejecting for combination treatment. Methods and materials From April 2002 to July 2010, 83 patients with stage II-III NSCLC, aged over 60 years, treated by RT alone with a curative aim were analyzed. Radiation was targeted to the primary tumor and clinically involved lymph nodes. A total dose of 66 Gy in 30 fractions (2.2 Gy/fraction) was delivered once daily (5 fractions weekly). One month after completing RT, initial tumor responses were evaluated. Results Median age of patients was 73 years (range, 60 – 82 years). The median survival time was 18.6 months (range, 2–135). The actuarial overall survival rates at 2 and 3 years were 39 % and 23 %, and cause-specific survival rate at 2 and 3 years were 57 % and 47 %, respectively. When primary tumor was controlled, the 2- and 3-year CSS were 56 % and 45 %, but 32 % and 23 % in those patients with local failure, respectively (P  = 0.017). Additionally, the local control rate was associated with the initial tumor response (P  = 0.01). No patient experienced grade 4+ toxicity. Conclusions For stage II-III NSCLC patients aged over 60 years and unfit or rejecting for combination treatment, RT alone showed promising result. Long-term disease control can be expected if an early tumor response to radiation is achieved, which could result in improved overall survival rates.